2019
DOI: 10.3390/cancers11071006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA Repair Mechanisms and Induction of Apoptosis in Triple Negative Breast Cancer Cells Expressing the Human Herpesvirus 6 U94

Abstract: Triple-negative breast cancer (TNBC) accounts for 15–20% of all breast cancers. In spite of initial good response to chemotherapy, the prognosis of TNBC remains poor and no effective specific targeted therapy is readily available. Recently, we demonstrated the ability of U94, the latency gene of human herpes virus 6 (HHV-6), to interfere with proliferation and with crucial steps of the metastatic cascade by using MDA-MB 231 TNBC breast cancer cell line. U94 expression was also associated with a partial mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Reported findings on these aspects regarding the putative actions of HHV-6 U94 are summarized in Table 1. In vitro studies [129] As to the viral life cycle, reported U94 functions include virus latency, integration, and reactivation; however, more information would be needed to precisely define its role and mechanism of action. Large-scale population studies, as well as systemic monitoring of iciHHV-6, could provide conclusive answers on the biological mechanisms involved in U94 action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported findings on these aspects regarding the putative actions of HHV-6 U94 are summarized in Table 1. In vitro studies [129] As to the viral life cycle, reported U94 functions include virus latency, integration, and reactivation; however, more information would be needed to precisely define its role and mechanism of action. Large-scale population studies, as well as systemic monitoring of iciHHV-6, could provide conclusive answers on the biological mechanisms involved in U94 action.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, U94 has been shown to inhibit proliferation, invasion, and angiogenesis (also in glioma) [128], downregulating proangiogenic factors and MMPs, thus confirming, in this tumor type as well, that it might a potential target for therapeutic intervention. In addition, U94 was recently shown to inhibit DNA damage repair mechanisms and induce apoptosis in triple-negative breast cancer cells [129], which account for about 15% of breast cancers. Interestingly, U94 altered the expression of several proteins involved in intrinsic apoptosis, such as Bcl-2, Bad, caspase-3, caspase-9, and PARP, and inhibited the cholesterol biosynthesis pathway.…”
Section: U94 Effects In Cells and Tissuesmentioning
confidence: 99%
“…Of late, our group demonstrated U94 to be a DDR inhibitor as it displays anticancer activity in MDA-MB-231 cells by downregulating DDR genes, cholesterol biosynthesis, and cell cycle, out of which cyclin-dependent kinase inhibitor 3 (CDKN3), Non-SMC Condensin II Complex Subunit G2 (NCAPG2), Ndc80 kinetochore complex component (NUF2), and High Mobility Group Box 1 (HMGB1), being the major ones. U94-mediated DDR inhibition likely occurs through downregulation of Bcl-2 and upregulation of Bax-, Bad-levels, Poly (ADP-ribose) polymerase (PARP) cleavage, and caspase-9-exerted apoptotic cell death via intrinsic apoptotic pathway activation [ 34 ]. The anticancer function of the viral protein was also investigated and confirmed in other triple-negative human breast cancer cell lines like MDA-MB 468 and BT-549 cells.…”
Section: Human Viral Proteins As Anticancer Agentsmentioning
confidence: 99%
“…The 26 original research articles covered 13 different cancer types including melanoma [ 1 , 2 , 3 , 4 ], breast cancer [ 5 , 6 , 7 , 8 ], colorectal cancer (CRC) [ 9 , 10 , 11 ], hepatocellular carcinoma [ 12 , 13 , 14 ], glioblastoma [ 15 , 16 ], non-small cell lung cancer (NSCLC) [ 17 , 18 ], prostate cancer [ 19 ], ovarian cancer [ 20 ], pleural mesothelioma [ 21 ], cervical cancer [ 22 ], Leukemia [ 23 ], adenoid cystic carcinoma [ 24 ], and vulvar cancer [ 25 ]. While these studies looked at a broad range of cancer therapies including cytotoxic chemotherapy [ 7 , 8 , 11 , 16 , 20 ], electrochemotherapy [ 25 ], radio therapy [ 2 , 4 , 18 ], proton beam therapy [ 24 ], and oncolytic virus therapy [ 6 ], the most studied are targeted therapies with various means. The cellular process being targeted include glucose metabolism [ 19 ], cell signaling [ 5 ], endoplasmic reticulum (ER) stress [ 21 ], autophagy [ 12 ], angiogenesis [ 10 ], DNA repair [ 4 , 6 ], apoptosis [ 11 ], and microRNA [ 10 , 26 ].…”
mentioning
confidence: 99%
“…While these studies looked at a broad range of cancer therapies including cytotoxic chemotherapy [ 7 , 8 , 11 , 16 , 20 ], electrochemotherapy [ 25 ], radio therapy [ 2 , 4 , 18 ], proton beam therapy [ 24 ], and oncolytic virus therapy [ 6 ], the most studied are targeted therapies with various means. The cellular process being targeted include glucose metabolism [ 19 ], cell signaling [ 5 ], endoplasmic reticulum (ER) stress [ 21 ], autophagy [ 12 ], angiogenesis [ 10 ], DNA repair [ 4 , 6 ], apoptosis [ 11 ], and microRNA [ 10 , 26 ]. The molecules being targeted include HER2 [ 5 ], VEGF [ 10 ], p53 [ 4 , 13 , 18 ], CDK [ 14 ], BCR-ABL1 and PAK1/2 [ 23 ], PARP1/HMGB1 [ 12 ], mir-221 [ 26 ], miR-31-5p [ 10 ], TIMP-1 [ 17 ], Fox3a [ 8 ], and FOXC1 [ 10 ].…”
mentioning
confidence: 99%